Behavioural Predictors of the Meta-cognitive Aspects of Thinking in the Process of Solving Super-complex Tasks: A Case Study of Middle and Senior Preschool Children - Chernyavskaya, Valentina S.; Samoylichenko, Alexander K. (Procedia, social and behavioral sciences, 2016)
This article offers an explanation and study of the meta-cognitive aspects of thinking which are examined as predictors of the meta-cognitive results of pre-school child education and development. The article also describes the analysis of the goals of the Federal Education Standards for pre-school education. The goals are achieved through creating conditions for forming an object-oriented learning environment for children of the pre-school age. Such meta-cognitive aspects of thinking as meta-cognitive control and meta-cognitive learning are viewed as prerequisites of meta-subject results. By studying the process of solving the Tower of Hanoi puzzle it concludes that the process of solving super-complex tasks triggers the regulatory and self-learning aspects of thinking. It proves that behavioural factors that predetermine the results of manifested meta-cognitive factors of thinking are verbalization of the knowledge about successful task solving, a flexible strategy of task solving; a sustainable positive emotional background during the process of solving a task.